Criminal Liability of the Press in Election Reporting: A Normative Analysis of Press Offences and Electoral Offences - Dwiyanto, Hendri; Zainal Arifin; Agus Manfaluthi; Zico Junius Fernando (The Indonesian Journal of International Clinical Legal Education, 2025)
This study aims to normatively analyze the criminal liability of the press in reporting on general elections in Indonesia, focusing on the application of the lex specialis principle, legal certainty, and the protection of press freedom. The main issues examined are the normative conditions under which criminal provisions in Law Number 7 of 2017 on General Elections can be applied to the press, and how the limits of media criminal liability are determined within the context of press freedom guaranteed by Law Number 40 of 1999 on the Press. The research employs a normative juridical method, drawing on statutory, conceptual, and case approaches. The findings indicate that criminal sanctions may be imposed on the media only if there is evidence of deliberate political intent and direct involvement in covert campaign activities or in the dissemination of misleading information intended to influence election outcomes. Within this framework, the lex specialis derogat legi generali principle establishes the Press Law as the specific regulation that must take precedence in resolving news disputes before criminal prosecution. The principle of legal certainty demands a clear distinction between ethical and criminal violations, while the principle of press freedom protection ensures that law enforcement is not used as a repressive tool against the media’s social control function. This study recommends strong coordination among the Election Supervisory Agency (Bawaslu), the Press Council, and law enforcement authorities to delineate the boundaries of press criminal liability, enabling electoral law enforcement without undermining press freedom, a cornerstone of democracy.